Solvent-Free Pyrolysis Strategy for the Preparation of Biomass Carbon Dots for the Selective Detection of Fe3+ Ions - Chen, Menglin; Zhai, Jichao; An, Yulong; Li, Yan; Zheng, Yunwu; Tian, Hao; Shi, Rui; He, Xiahong; Liu, Can; Lin, Xu (Frontiers in Chemistry, 2022)
Biomass carbon dots (BCDs) have the advantages of being nontoxic, low cost and simple to prepare, have excellent optical properties, good biocompatibility and stability, and therefore have broad application prospects in areas such as heavy metal ion detection and optoelectronic devices. Through this research, a simple, green, solvent-free method of preparing BCDs was developed. Carbon dots (CDs) with good water solubility and certain fluorescence properties were prepared by a solvent-free pyrolysis method at different temperatures using two abundant components (cellulose and lignin) of biomass resources as carbon sources. Both the cellulose CDs prepared at 300 °C and the lignin CDs prepared at 350 °C exhibited high quantum yields of 11.7% and 23.4%, respectively, a result that was mainly due to the high degree of graphitization of both CDs. The analysis and results demonstrated the selectivity of CDs for the detection of various metal ion solutions. In particular, CDs are sensitive to Fe3+ and can be used as a fluorescent sensor for the detection of Fe3+, providing a more efficient, sustainable alternative for metal ion detection.